2022
DOI: 10.22207/jpam.16.4.43
|View full text |Cite
|
Sign up to set email alerts
|

Pectinase Production by Aspergillus niger and Its Applications in Fruit Juice Clarification

Abstract: Pectinases (EC 3.2.1.15) are a class of enzymes that catalyze the depolymerization or de-esterification reactions that degrade pectic substances. In the present study, we have isolated the Aspergillus niger strain from soil samples, in India and evaluated pectinase production. The highest pectinase producing A. niger strain was further evaluated and optimized with various agricultural wastes. Plackett-Burman design (PBD) and Central composite design ‘(CCD)’ were used to determine the best parameters for maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Moreover, the non‐fermented OP contained a higher concentration of monomeric sugars than WOP, which were partially removed during the washing step. In addition, despite the fungus growth being limited at the high temperature of hydrolysis (50°C), in the literature it is reported that some fungal species can grow at temperatures as high as 50 °C 35,36 . Thus, part of the monosaccharides released in the hydrolysis could have been consumed by the fungus, being this reduction more important at the highest proportion of fermented WOP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the non‐fermented OP contained a higher concentration of monomeric sugars than WOP, which were partially removed during the washing step. In addition, despite the fungus growth being limited at the high temperature of hydrolysis (50°C), in the literature it is reported that some fungal species can grow at temperatures as high as 50 °C 35,36 . Thus, part of the monosaccharides released in the hydrolysis could have been consumed by the fungus, being this reduction more important at the highest proportion of fermented WOP.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, despite the fungus growth being limited at the high temperature of hydrolysis (50°C), in the literature it is reported that some fungal species can grow at temperatures as high as 50 °C. 35,36 Thus, part of the monosaccharides released in the hydrolysis could have been consumed by the fungus, being this reduction more important at the highest proportion of fermented WOP. Similar results were observed in a previous study carried out by Marzo et al 20 in which the maximum concentration of reducing sugars was lower when the fermented/unfermented ratio of sugar beet changed from 14.3%/85.7% to 50%/50%.…”
Section: Enzymatic Hydrolysis Of Orange Peels (Ops)mentioning
confidence: 99%